Analisis Pengambilan Keputusan dalam Kendala di UMKM Dapur Nongbella - Glenn Sendjaja; Muhammad Syahroni; Refy Febri Pratama; Zulfi Nashrullah; Ujang Suherman (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Micro, small, and medium enterprises (MSMEs) in Indonesia hold a significant position in the economy; however, they frequently encounter obstacles in making efficient decisions. The study of decision-making theory focuses on identifying the optimal alternatives to achieve specific objectives. This process entails recognizing problems, collecting relevant data, and assessing various options. Different approaches are utilized, such as rational theory, which emphasizes cost-benefit analysis, and incremental theory, which prioritizes gradual adaptations to prior decisions. Moreover, cognitive elements and social settings influence decision-making, with the bounded rationality model underscoring the constraints of available information and individual cognitive capacities. Studies indicate that implementing decision-making theories can assist MSMEs in overcoming limitations in accessing information and analytical resources. Management information systems (MIS) are instrumental in enhancing both the efficiency and effectiveness of decisions while also promoting business sustainability in the digital age. By comprehending and integrating these theories, MSMEs can elevate the quality of their decision-making processes and strengthen their competitiveness in the global market.